2020
DOI: 10.30827/portalin.v0i36.16228
|View full text |Cite
|
Sign up to set email alerts
|

Subtitling and dubbing as teaching resources in CLIL in Primary Education: The teachers’ perspective

Abstract: This paper explores the use of Audiovisual Translation (AVT) as a didactic tool in schools of Primary Education. The investigation of active subtitling and dubbing in formal contexts has delivered promising results concerning students’ motivation, the improvement of translation skills, and the promotion of oral and written comprehension and production. However, research in the field has predominantly concentrated on university students, and there is a paucity of studies scrutinising Primary Education. Also, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
1
9
0
8
Order By: Relevance
“…The use of audiovisual media plays an important role in overcoming students' problems, especially in learning foreign languages in terms of students' fluency (Pamungkas, 2019). The results of this study indicate that the use of audiovisual media based on voiceover translation in motivating and overcoming the negative psychology of students are in line with research that has been conducted by (Fernández-Costales, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…The use of audiovisual media plays an important role in overcoming students' problems, especially in learning foreign languages in terms of students' fluency (Pamungkas, 2019). The results of this study indicate that the use of audiovisual media based on voiceover translation in motivating and overcoming the negative psychology of students are in line with research that has been conducted by (Fernández-Costales, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…Studies in the field have reported empirical evidence to support didactic claims that AVT favours vocabulary retention (Danan, 2010;Lertola, 2019b), intercultural awareness (Borghetti, 2011;Borghetti & Lertola, 2014), productive skills (Talaván & Costal, 2017;Talaván & Rodríguez-Arancón, 2018), and fluency (Herrero et al, 2017;Sánchez-Requena, 2016). Recent contributions have also focused on the potential of AVT in bilingual education (Fernández-Costales, 2021b), the combination of subtitling and dubbing in language teaching (Fernández-Costales, 2021a;Talaván & Ávila-Cabrera, 2015), or the promotion of creativity through active AVT (Talaván, 2019).…”
Section: Active Subtitling In the Classroommentioning
confidence: 99%
“…Furthermore, it should be noted that the pilot study presented was implemented in a translation course and not a language subject, and the possible relation with language syllabi has not been directly explored in the TRADILEX project. However, recent studies confirm didactic AVT may be integrated into language courses, and AVT tasks can be framed within the curriculum of Primary Education (Fernández-Costales, 2021a, 2021b. Captioning and revoicing activities can also be used in the bilingual education (CLIL) syllabi of non-language subjects, where students learn curricular contents through the L2.…”
Section: Final Remarksmentioning
confidence: 99%
“…Didactic Audiovisual Translation (AVT) is a technologybased active pedagogical resource (as students produce subtitles or dub video extracts, etc.) that can enhance foreign language learning and can be employed as an effective tool in face-to-face, online, and blended contexts (Lertola, 2019;Talaván, 2020;Fernández-Costales, 2021;Baños et al, 2021). Most AVT modes can be used either individually or combined to develop communicative and transferable skills.…”
Section: Introductionmentioning
confidence: 99%